Clinical Review on Abdominal Acupuncture Treating Dysmenorrhea - Ting, Fei Jian (2015)
Dysmenorrhea has been known to be the most commonly seen disease in gynecology field. According to a survey done in KL by Li Ping Wong in the year 2009, about 75% of female reaching menarche experienced different level of dysmenorrhea, and about 50% of them claimed that it has affected their focus in normal daily activities. Hence this study has and important social and economy value. Abdominal acupuncture has been chosen to be used in treating dysmenorrhea as it cost less and has very little side effect. This study aims to explore and analyze the literature review on treatment principle and efficacy of Abdominal Acupuncture towards dysmenorrhea, in 2 course of treatment, with each course consist of at least 8 treatments in one menstrual cycle.